Basinal and planform characteristics of the Kodku and the Godavari Rivers, Kathmandu, Central Nepal - Tamrakar, Naresh Kazi; Bajracharya, Ramita (Bulletin of the Department of Geology, 2013)
The rivers of the Kathmandu Basin are vulnerable to flash floods and disturbances caused by anthropogenic as well as climatic changes. Two southern tributaries of the Bagmati River: the Kodku and the Godavari Rivers, have been considered for their (i) watershed-scale geomorphic parameters such as relative relief, drainage texture and stream order, (ii) stretchscale planform parameters such as sinuosity (K), meander belt width (Wblt), meander wavelength (Lm) and radius of curvature (Rc), and (ii) longitudinal profiles and slopes. Both Kodku and the Godavari Rivers are elongate basins with wide ranges of the watershed-scale parameters. The Godavari River is longer, larger and more sinuous compared to the Kodku River. The development of the patterns of the fifth order main stem stretches of both rivers with respect to the stream slopes, and asymmetric patterns of the meander loops indicate anomalous growth of the river stretches. DOI: http://dx.doi.org/10.3126/bdg.v15i0.7414 Bulletin of the Department of Geology, Vol. 15, 2012, pp. 15-22